Membangun Resiliensi Spiritual Kristen Pada Anak Berkebutuhan Khusus Ditinjau Dari Pandangan Teologi Disabilitas - Suardin Zai; Yusuf Setiawan Sudarso Kusumo; Suarman Zai (LPPM - STT Kadesi Bogor, 2024)
Children with special needs are one of the most vulnerable groups to experience emotional stress and mental disorders. Therefore, building spiritual resilience becomes extremely important to help them better face life's challenges. This research aims to explore ways to build Christian spiritual resilience in children with special needs from the perspective of disability theology. Disability theology offers a new perspective on disability as part of God's plan and acknowledges the dignity and potential of these children. Through in-depth literature study and theological analysis, this research will identify principles and practices that can help develop strong self-confidence, courage, and meaning in life for children with special needs in the context of the Christian faith. The findings of this research are expected to provide valuable insights for educators, counselors, and religious leaders in accompanying children with special needs to grow holistically, physically, mentally, and spiritually.